2007
DOI: 10.1266/ggs.82.447
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular analysis of the temperature-sensitive mutant un-17 carrying a mutation in the gene encoding poly(A)-polymerase in Neurospora crassa

Abstract: The un-17 mutant was originally isolated as an irreparable temperature-sensitive (ts) mutant in Neurospora crassa. Early experiments showed that cells of this mutant immediately stopped growing and died when the temperature of the culture was shifted from a permissive temperature (25°C) to non-permissive temperature (35°C). This ts phenotype is suppressed by addition of cycloheximide or in some conditions of growth repression. Even at the permissive temperature, it shows a female sterile phenotype and is defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In this study, we found that Fg06103 and Fg02043 may be essential in F. graminearum (Table S3), but their orthologs are nonessential in A. nidulans (Son & Osmani, ), suggesting that other unidentified phosphatases may share similar functions with the Fg06103 and Fg02043 orthologs in A. nidulans . Similarly, the ortholog of Fg01918 is essential in N. crassa (Tanaka et al ., ), but ΔFg01918 of F. graminearum grew as well as the wild‐type strain. Thus, it would be interesting to further characterize these phosphatases with species‐specific functions in the pathogenic fungi.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we found that Fg06103 and Fg02043 may be essential in F. graminearum (Table S3), but their orthologs are nonessential in A. nidulans (Son & Osmani, ), suggesting that other unidentified phosphatases may share similar functions with the Fg06103 and Fg02043 orthologs in A. nidulans . Similarly, the ortholog of Fg01918 is essential in N. crassa (Tanaka et al ., ), but ΔFg01918 of F. graminearum grew as well as the wild‐type strain. Thus, it would be interesting to further characterize these phosphatases with species‐specific functions in the pathogenic fungi.…”
Section: Discussionmentioning
confidence: 97%
“…Immunoprecipitation and Western blotting were carried out as described (Kawabata et al, 2007;Tanaka et al, 2007;Wakabayashi et al, 2010). Conidia (1 Â 10 8 ) were incubated in minimal liquid medium (20 ml) for 12 h at 30°C with or without 0.76 mg/ml HU.…”
Section: Western Blottingmentioning
confidence: 99%
“…Immunoprecipitation and Western blotting were carried out as described by Kawabata et al (2007) and Tanaka et al (2007). Conidia (1 Â 10 8 ) that had been incubated in minimal liquid medium (20 ml) for 6 h at 25°C were treated with 1 ll/ml MMS for 3 h at 25 or 37°C.…”
Section: Western Blottingmentioning
confidence: 99%